Res publica constituta : Actium, Apollo, and the accomplishment of the triumviral assignment - Lange, Carsten Hjort. (Impact of Empire, 2009)
The years surrounding the decisive battle of Actium in 31 BC, and the various measures undertaken by the victor Augustus to create and legitimate a new system of government in Rome are among the most discussed aspects of Roman history. This book re-evaluates Augustus' rise to power, first as triumvir along with Antonius and Lepidus, and then as sole ruler, focusing particularly on the part played by propaganda and ideological claims. Augustus is shown to have acknowledged the Actium war as a civil as well as an external war, and the commemorations of the battle at the site and in Rome are re-assessed, along with the role ascribed to Apollo in the victory. The celebrated settlement of 28-27 BC is shown to have constituted the accomplishment of the triumviral assignment.